X-ray resonant scattering study of the magnetic phase diagram of multiferroic TbMnO3 - Walker, H; Ewings, R; Fabrizi, F; Mannix, D; Mazzoli, C; Wilkins, S; Paolasini, L; Prabhakaran, D; Boothroyd, A; McMorrow, D (2009)
We present the magnetic phase diagram of multiferroic TbMnO3 for H ∥ b determined using X-ray resonant scattering at the Tb L3-edge. Investigations of two different magnetic domains, C-type and F-type, demonstrate very similar behaviour in high applied magnetic fields, with a low temperature incommensurate to commensurate transition at H ≃ 4.5 T, concurrent with the polarisation flop observed in bulk magnetoelectric measurements. © 2009 Elsevier B.V. All rights reserved.